The structure and function of the global citrus rhizosphere microbiome. Issue 1 (December 2018) - Xu, Jin; Zhang, Yunzeng; Zhang, Pengfan; Trivedi, Pankaj; Riera, Nadia; Wang, Yayu; Liu, Xin; Fan, Guangyi; Tang, Jiliang; Coletta-Filho, Helvécio; Cubero, Jaime; Deng, Xiaoling; et al.
Abstract Citrus is a globally important, perennial fruit crop whose rhizosphere microbiome is thought to play an important role in promoting citrus growth and health. Here, we report a comprehensive analysis of the structural and functional composition of the citrus rhizosphere microbiome. We use both amplicon and deep shotgun metagenomic sequencing of bulk soil and rhizosphere samples collected across distinct biogeographical regions from six continents. Predominant taxa includeProteobacteria, Actinobacteria, Acidobacteria andBacteroidetes . The core citrus rhizosphere microbiome comprisesPseudomonas, Agrobacterium, Cupriavidus, Bradyrhizobium, Rhizobium, Mesorhizobium, Burkholderia, Cellvibrio, Sphingomonas, Variovorax andParaburkholderia, some of which are potential plant beneficial microbes. We also identify over-represented microbial functional traits mediating plant-microbe and microbe-microbe interactions, nutrition acquisition and plant growth promotion in citrus rhizosphere. The results provide valuable information to guide microbial isolation and culturing and, potentially, to harness the power of the microbiome to improve plant production and health. Research on plant root-associated microbial communities may help develop more efficient or sustainable crop production methods. Here the authors analyse the citrus rhizosphere microbiome, using both amplicon and deep shotgun metagenomic sequencing of samples collected across six continents.